Internalization of Ahlussunnah Wal Jama'ah Values in the Formation of Students' Character Through Nu-an Subjects in Ma Nawa Kartika Selogiri - Abdulloh Ibnu Muhammad; Ali Mahbub; mukminin (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
Globalization has the potential to cause complex and worrying negative impacts, particularly on the character formation of the younger generation. Therefore, ahlussunnah wal jama'ah offers itself as a solution based on the values of tawasuth (moderation), tawazun (balance), tasamuh (tolerance), i'tidal (justice), and amar ma'ruf nahi munkar (enjoining good and forbidding wrong), to shape the character of the younger generation. At MA Nawa Kartika, the Ke-NU-an subject is taught, in which these five values of ahlussunnah wal jama'ah are instilled. However, even though it has become a mandatory curriculum at MA Nawa Kartika, there are still students who exhibit poor character, such as ghasab (usurping rights) and quarreling with friends due to differing opinions. This research aims to (1) describe the ahlussunnah wal jama'ah values being taught, (2) describe the process of internalizing ahlussunnah wal jama'ah values, and (3) analyze the supporting and inhibiting factors for the internalization of ahlussunnah wal jama'ah values. To answer these questions, this research uses a descriptive qualitative approach with a field study type. Based on the research findings, it was discovered that: (1) the ahlussunnah wal jama'ah values taught include the values of tawasuth, tawazun, tasamuh, i'tidal, and amar ma'ruf nahi munkar. (2) The process of value internalization is carried out in three stages: the value transformation stage, the value transaction stage, and the trans-internalization of value stage. (3) Supporting factors come from teachers as role models and facilitators who provide examples of real behavior, as well as the madrasah and foundation that provide consistent regulations connected to the learning of Ahlussunnah wal Jama'ah values. Facilities such as student worksheets, LCD projectors, textbooks, and Ahlussunnah wal Jama'ah books also support the learning process. Inhibiting factors come from the family backgrounds of students who come from different mass organizations or schools of thought, as well as the limited class hours for Ke-NU-an subjects.